Testicular Cancer in Infertile Men With and Without Testicular Microlithiasis: A Systematic Review and Meta-Analysis of Case-Control Studies - Barbonetti, Arcangelo; Martorella, Alessio; Minaldi, Elisa; D'Andrea, Settimio; Bardhi, Dorian; Castellini, Chiara; Francavilla, Felice; Francavilla, Sandro (Frontiers in Endocrinology, 2019)
Background: An association between testicular microlithiasis (TM) and both carcinoma in situ (CIS) of the testis and testicular germ cell tumors (TGCTs) has been reported. Furthermore, TM seems to be significantly more prevalent in men with male-factor infertility, representing itself a risk factor for TGCT. Nevertheless, the evidence of the association of TM with a higher prevalence of testicular cancer in infertile men remains inconclusive. The aim of this study was to systematically evaluate whether, and to what extent, TM is associated to a significantly higher prevalence of testicular cancer in infertile males. Methods: A thorough search of MEDLINE, SCOPUS, CINAHL, WEB OF SCIENCE and Cochrane Library databases was carried out to identify case-control studies comparing the prevalence of testicular cancer in infertile men with and without TM. Methodological quality of the studies was assessed using the Newcastle-Ottawa Scale. In the absence of heterogeneity, odds ratios (ORs) with 95% confidence intervals (CIs) for testicular cancer were combined using a fixed effect model. Funnel plots and trim-and-fill analysis were used to assess publication bias. Results: Eight studies met the inclusion criteria and provided information on 180 infertile men with TM and 5088 infertile men without TM. The pooled OR indicated that the presence of TM is associated with a ~18-fold higher odd for testicular cancer (pooled OR:18.11, 95%CI: 8.09, 40.55; P<0.0001). No heterogeneity among the studies was observed (Pfor heterogeneity=0.99, I-square=0%). At the sensitivity analysis, similar pooled ORs and 95%CIs were generated with the exclusion of each study, indicating the high degree of stability of the results. The funnel plot revealed a possible publication bias and the trim-and-fill test detected two putative missing studies. Nevertheless, even when the pooled estimate was adjusted for publication bias, there was a still significantly higher odd for testicular cancer in the TM group (adjusted pooled OR: 16.42, 95%CI: 7.62, 35.37; P<0.0001). Conclusions: In infertile men the presence of TM is associated to an ~18-fold higher prevalence of testicular cancer. Longitudinal studies are warranted to elucidate whether this cross-sectional association actually reflects a higher susceptibility of infertile men with TM to develop testicular cancer over time.